Can the consumption-free nonexpected utility model solve the risk premium puzzle? An empirical study of the Japanese stock market - Myong-Il Kang (Osaka University, Institute of Social and Economic Research (ISER), 2010)
This paper investigates whether the consumption-free two-beta intertemporal capital asset-pricing model developed by Campbell and Vuolteenaho (2004) is able to solve the risk premium puzzle in the Japanese stock market over the period 1984-2002. Using the cash flow and discount rate betas as risk factors, the model is able to explain about half of the market returns by selection of suitable vector autoregression variables. On this basis, the model proposed solves the risk premium puzzle in Japan, thereby suggesting that Japanese investors are less risk averse than US investors. However, a model including only the cash flow beta better explains returns than a model with both betas. The analysis also tests and rejects the simple capital asset-pricing model in Japan.
Keywords: G12; 330; risk premium puzzle; nonexpected utility; CAPM; Börsenkurs; Risikoprämie; Erwartungsnutzen; CAPM; Schätzung; Japan